Islamic Students Understanding about the Center of the Earth in Science and Islam Perspective - Mubarok, Husni (http://jagadalimussirry.com/, 2019)
The center of the earth and the shape of the earth have a very close relationship, theories have been widely discussed about the concept of both things. Starting from the earth shapes are flat globe and elliptical, besides that the center of the earth in the North Pole, Mecca, the core of the earth even in the archipelago (Indonesia). This study used a qualitative research method was considered in helping the researcher to comprehend better the process of constructing meaning. The study used an interview and a written questionnaire. There are fifty participants in this study, the participants from Islamic student of Jagad Alimussirry Islamic boarding school. The result of this study shown that the majority of Islamic students have a strong understanding of the earth shape and the position of the earth center, which is viewed from the perspective of science and Islam. Most of respondents have an understanding that the shape of the earth is globe with its central position in the city of Mecca.